MPM Berbasis Konteks dan Strategi Pembelajaran Matematika Realistik Bagi Guru Matematika Tingkat SMP - Nasrullah Nasrullah; Wahidah Sanusi; Muhammad Abdy (DEDIKASI, 2020)
Partners of the Community Partnership Program (PKM) are the Mathematics MGMP of Takalar Regency. The problems are 1) The teacher has not maximized active learning activities in the classroom 2) The teacher has not maximally utilized media and strategies in learning activities. For implementation, participants are involved in training activities whose implementation includes material presentation and practical activities. In presenting the material, participants are given materials on the concept of context-based learning media and realistic mathematics learning strategies. However, with the consideration of the Covid-19 pandemic so that the implementation of this training is carried out in virtual or other terms in the network (online). In the practical activity section, participants carry out practical activities for the preparation and development of learning contexts and learning scenarios with Realistic Mathematics learning strategies. To support the implementation of the activity, participants were given the opportunity to express their opinions with this activity, context-based manipulative learning media, and the Realistic Mathematical Approach (PMR). The result is 16.7% who know somewhat, meaning that they have read but have not implemented it in the learning class. The same thing happened for 33.3% where the participants knew enough, in other words, they understood PMR well but were not able to keep pace with its development. The remaining 50% have carried out this learning in their respective classes.